2015
DOI: 10.1007/s10902-015-9666-0
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Coping in Hindu Adolescents in India

Abstract: This exploratory study examined the relations between approach and avoidance coping behaviors and general life satisfaction in a sample of 248 Hindu adolescents from an urban area in India. The major findings were threefold. First, gender differences were observed, with females reporting more frequent use of the strategies of seeking social support, direct problem solving, and internalizing behaviors. Second, using multiple regression analyses, the coping behaviors of problem solving and externalizing behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…A review of multiple regression analysis results indicates that the model used to examine the predictive effect of demographic variables on positivity was not significant [F (3,264) = .55, p>.05)] and all demographic variables explained 1% of variance on positivity scores (R= .08, R 2 = .01). The predictive power of perceived social support and coping styles, as independent research variables, on positivity was examined through multiple standard regression analysis method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of multiple regression analysis results indicates that the model used to examine the predictive effect of demographic variables on positivity was not significant [F (3,264) = .55, p>.05)] and all demographic variables explained 1% of variance on positivity scores (R= .08, R 2 = .01). The predictive power of perceived social support and coping styles, as independent research variables, on positivity was examined through multiple standard regression analysis method.…”
Section: Resultsmentioning
confidence: 99%
“…Gąsior, Biedrzycka, Chodkiewicz, Ziółkowski, Czarnecki, Juczyński, and Nowakowska-Domagała (2016) found positive significant relationships between coping with stress and life satisfaction. Antaramian, Kamble, and Huebner [3] revealed in a study conducted with adolescents that more females than males used seeking assistance among coping styles and problem solving as a coping style predicted life satisfaction. Li, Delvecchio, Lis, Nie, and Di Riso [58] found that negative coping was negatively and positive coping was positively significantly related with life satisfaction.…”
mentioning
confidence: 99%
“…Avoidant coping approaches were positively related to pessimism (Puskar et al, 1999) and higher risk for internalizing and externalizing problems (Liu et al, 2004). Externalizing behaviors, as examples of avoidance behaviors, were associated with lower life satisfaction (Antaramian et al, 2016). Also, the negative coping strategies were related to the decrease in resilience (Bedel & Güler, 2019) and the increase in depression, anxiety, anger, hostility, and aggression (Sun, Sun, Jiang, Jia, & Li, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Coping strategies affect well-being in multiple ways. For example, active coping is considered as the most effective and favorable coping style because it is associated with positive outcomes (Carothers et al, 2016) such as optimism (Puskar et al, 1999), positive affect (Coyle & Vera, 2013), reduced risk for internalizing and externalizing problems (Liu, Tein, & Zhao, 2004), high well-being (Freydenberg & Lewis, 2009), resilience (Bedel & Güler, 2019), and life satisfaction (Antaramian, Kamble, & Huebner, 2016). On the contrary, avoidant and negative coping were found to be associated with undesirable outcomes such as lower levels of wellbeing (Cicognani, 2011;Freydenberg & Lewis, 2009;Miller Smedema, Catalano, & Ebener, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In view of the variety of stressors that adolescents face during this period of life, such as biological changes, peer and academic pressures, and increasing independence from parents, 10 LS in this population has become the object of growing research attention. 7,[11][12][13][14][15] Key to such research is the hypothesis that, in order to promote positive functioning in adolescence, one must not only gain insight into the typical problems of this phase of development but also focus on factors that may act as resources in how adolescents cope with adversities. 9 Childhood maltreatment has been described in the literature as an important predictor of psychopathology.…”
Section: Introductionmentioning
confidence: 99%